600 fs mode-locked solid-state laser based on few-layer WS2 saturable absorber. (13th March 2018) - Li, Xiaowen; Qian, Jianqiang; Ai, Fei
Abstract: We report on the passive mode-locking operation of a solid-state laser based on tungsten disulfide (WS2 ) saturable absorber (SA). 600 fs pulses were achieved with an average output power of 0.438 W, corresponding to a pulse energy of 3.9 nJ and a pulse peak power of 5.7 kW, respectively. To the best of our knowledge, these are the shortest pulses ever obtained from WS2 SA mode-locked solid-state lasers. The results indicate the promising potential of WS2 as SA for generating femtosecond laser pulses.